Evaluation of the Relationship between Personality and Conservatism of Investors in the Stock Exchange (Case Study: Insurance Companies) - Mohseni, Mahsa (2021)
The purpose of this research to "investigate the relationship between personality and conservatism of investors of insurance companies listed on the Tehran Stock Exchange." The present study was applied research in terms of purpose, which has employed a descriptive and correlational method. The statistical population of this research included all people who buy and sell shares of insurance companies listed on the Tehran Stock Exchange. According to Cochran's formula, the sample size was determined as much as 384 people collected by a simple random sampling method. The research instruments were the Conservative Questionnaire based on the Gribel and Leighton (1999) and McCrae and Costa (1985) five-factor personality questionnaire. The questionnaire’s validity was confirmed by 20 experts, and the reliability of all three questionnaires was acceptable for all three questionnaires due to Cronbach's alpha above 0.79. The data analysis was conducted using the Pearson correlation test and regression analysis. The results indicated a significant relationship between the investors’ personality and their conservatism in the Tehran Stock Exchange. There was also a significant relationship between all personality components except for extraversion with the investor’s conservatism in the Tehran Stock Exchange.